A real-time fMRI neurofeedback system for the clinical alleviation of depression with a subject-independent classification of brain states: A proof of principle study - Pereira, Jaime A.; Ray, Andreas; Rana, Mohit; Silva, Claudio; Salinas, Cesar; Zamorano, Francisco; Irani, Martin; Opazo, Patricia; Sitaram, Ranganatha; Ruiz, Sergio (Frontiers in Human Neuroscience, 2022)
Most clinical neurofeedback studies based on functional magnetic resonance imaging use the patient's own neural activity as feedback. The objective of this study was to create a subject-independent brain state classifier as part of a real-time fMRI neurofeedback (rt-fMRI NF) system that can guide patients with depression in achieving a healthy brain state, and then to examine subsequent clinical changes. In a first step, a brain classifier based on a support vector machine (SVM) was trained from the neural information of happy autobiographical imagery and motor imagery blocks received from a healthy female participant during an MRI session. In the second step, 7 right-handed female patients with mild or moderate depressive symptoms were trained to match their own neural activity with the neural activity corresponding to the “happiness emotional brain state” of the healthy participant. The training (4 training sessions over 2 weeks) was carried out using the rt-fMRI NF system guided by the brain-state classifier we had created. Thus, the informative voxels previously obtained in the first step, using SVM classification and Effect Mapping, were used to classify the Blood-Oxygen-Level Dependent (BOLD) activity of the patients and converted into real-time visual feedback during the neurofeedback training runs. Improvements in the classifier accuracy towards the end of the training were observed in all the patients (Session 4-1 Median=6.563%; Range=4.10 to 27.34; Wilcoxon Test (0), 2-tailed p=0.031). Clinical improvement also was observed in a blind standardized clinical evaluation (HDRS CE2-1 Median=7; Range 2 to 15; Wilcoxon Test (0), 2-tailed p=0.016), and in self-report assessments (BDI-II CE2-1 Median=8; Range -1 to 15; Wilcoxon Test (0), 2-tailed p=0.031). In addition, the clinical improvement was still present 10 days after the intervention (BDI-II CE3-2_Median=0; Range -1 to 2; Wilcoxon Test (0), 2-tailed p=0.50/ HDRS CE3-2 Median=0; Range -1 to 2; Wilcoxon Test (0), 2-tailed p=0.625). Although the number of participants needs to be increased and a control group included to confirm these findings, the results suggest a novel option for neural modulation and clinical alleviation in depression using noninvasive stimulation technologies.